El extractivismo de las algas pardas en el norte de Chile - Márquez, Raúl; Vásquez, Julio Alberto (European Review of Latin American and Caribbean Studies, 2020)
Abstract: The extractivism of brown algae in northern ChileThe extraction and collection of brown algae (huiros) showed an exponential increase in the early 2000s. This fishery is transformed into extractive due to the international demand for raw material for the production of alginate (a product widely used in the textile and food industries). Its analysis in terms of global value chain and extractivist logic highlights recurring aspects of these forms of appropriation of capitalist value: exploitation in cycles of abrupt rise and fall, environmental and socio-labour degradation, hierarchies and inequalities. It also shows other apparently more heterodox aspects such as the management of a natural resource participated by the collectors and the role of the state, or the relative isolation and the reduced size of the places where it is collected. Thus, this industry is a relevant case to delve into the complex dynamics of extractivism, especially in aspects of governance as a policy of co-management of artisanal resources on the coast of Chile. ResumenLa extracción y recolección de algas pardas (huiros) muestran un incremento exponencial a principios de los años 2000. Esta pesquería de recolección se transforma en una pesquería extractiva debido a la demanda internacional de materia prima para la producción de alginato (producto de amplio uso en las industrias textil y alimentaria). Su análisis en términos de cadena global de valor y lógica extractivista ilumina aspectos recurrentes de estas formas de apropiación del valor capitalista: la explotación en ciclos de alza abrupta y caída, la degradación ambiental y socio-laboral, las jerarquías y las desigualdades. Además muestra otros aspectos en apariencia más heterodoxos como la gestión de un recurso natural participado por los recolectores y el rol del Estado, o el aislamiento relativo y el tamaño reducido de los lugares donde se recolecta. Por tanto, esta industria es un caso relevante para profundizar en las complejas dinámicas del extractivismo, especialmente en aspectos de la gobernanza como la política de co-manejo de recursos artesanales en la costa de Chile.